1982
DOI: 10.1103/physrevc.25.2619
|View full text |Cite
|
Sign up to set email alerts
|

Kaon scattering from C and Ca at 800 MeV/c

Abstract: Results from I(, +elastic and inelastic scattering from ' C and Ca are reported. The data were all taken at an incident momentum of 800 MeV/c over an angular range from 2' to 38'. The elastic data are compared to first-order optical model calculations in coordinate and momentum space; good qualitative agreement is obtained. The inelastic data (from ' C only) are compared to distorted-wave Born approximation calculations, and good agreement is found if "realistic" inelastic transition densities are used. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
58
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 29 publications
8
58
0
Order By: Relevance
“…They have obtained a momentum dependent potential in a dispersion approach at normal nuclear density, the potential depth is about 140 ± 20MeV at zero momentum, and decreases rapidly for higher momenta. In our previous work [5], we also found that the kaon nucleus optical potential has strong momentum dependence by fitting the only experimental data on the K − -C, K − -Ca scattering at P k = 800 MeV/c [6]. We indicated that the depth of real potential at the inner nuclei is (45 ± 5) MeV at P k = 800 MeV/c, which is much shallower than that at zero momentum in the RMF.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…They have obtained a momentum dependent potential in a dispersion approach at normal nuclear density, the potential depth is about 140 ± 20MeV at zero momentum, and decreases rapidly for higher momenta. In our previous work [5], we also found that the kaon nucleus optical potential has strong momentum dependence by fitting the only experimental data on the K − -C, K − -Ca scattering at P k = 800 MeV/c [6]. We indicated that the depth of real potential at the inner nuclei is (45 ± 5) MeV at P k = 800 MeV/c, which is much shallower than that at zero momentum in the RMF.…”
mentioning
confidence: 91%
“…The experimental data of the differential elastic cross sections for K − -12 C and K − -40 Ca at P K = 800 MeV/c [6] are used to determine the parameters κ = 0.275 GeV and β = (0.49, 0.44, 0.42) GeV (corresponding to W 0 = 50, 65, 80 MeV, respectively). In Fig.…”
mentioning
confidence: 99%
“…We note that the data of Ref. [4] was taken at a pion lab momentum of 800 MeV/c which is very near T π = 680…”
Section: B Important Features In the Eikonal Approximationmentioning
confidence: 99%
“…The pion-nucleus interaction at energies above the ∆ 33 resonance has received [2,3,4,5] much less attention. In this energy region (300 MeV ≤ T π ≤ 1 GeV), the pion has a much shorter wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected then [1] that K-nuclear interactions be well described, in terms of the free-space KN t matrix and the nuclear density ρ, by the first-order optical potential V opt = tρ. However, K + nucleus total cross section values [2][3][4][5][6][7] and reaction cross section values [7] derived from attenuation cross sections measured in transmission experiments, as well as elastic [8,9] and inelastic differential cross sections [8,10] and quasifree spectra [11], all point to a substantial departure of the order of 10-20% from the predictions of a simple tρ potential, even when many conventional nuclear medium effects are incorporated [12,13]. Several nonconventional medium effects have also been proposed to remedy the failure of the first-order optical potential approach, such as nucleon swelling [14], or density dependent vector meson masses [15], or polarizing the nuclear medium byNN excitations [16], or meson exchange currents [17,18], but as we shall discuss in the concluding section, none of these models provides a satisfactory solution to the discrepancy.…”
Section: Introductionmentioning
confidence: 99%